2005
DOI: 10.1128/jvi.79.9.5870-5874.2005
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA Is Required for the Association of APOBEC3G with Human Immunodeficiency Virus Type 1 Nucleoprotein Complexes

Abstract: APOBEC3G (APO3G) is a host cytidine deaminase that is incorporated into human immunodeficiency virus type 1 (HIV-1) particles. We report here that viral RNA promotes stable association of APO3G with HIV-1 nucleoprotein complexes (NPC). A target sequence located within the 5-untranslated region of the HIV-1 RNA was identified to be necessary and sufficient for efficient APO3G packaging. Fine mapping revealed a sequence normally involved in viral genomic RNA dimerization and Gag binding to be important for APO3G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
165
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(180 citation statements)
references
References 33 publications
(35 reference statements)
14
165
1
Order By: Relevance
“…APO3G is packaged into viruses or virus-like particles in a process that involves nucleocapsid protein and viral genomic RNA (4,5,7,17,21,32,39,44). Moreover, we previously reported that APO3G packaged in the presence of viral genomic RNA stably associates with viral nucleoprotein complexes and is resistant to detergent treatment while APO3G packaged in the absence of viral genomic RNA is detergent sensitive and presumably not core associated (17). It is conceivable that the lack of antiviral activity of APO3G C288S/C291A when expressed from stably transfected HeLa cells is due to aberrant packaging of the protein into HIV-1 particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…APO3G is packaged into viruses or virus-like particles in a process that involves nucleocapsid protein and viral genomic RNA (4,5,7,17,21,32,39,44). Moreover, we previously reported that APO3G packaged in the presence of viral genomic RNA stably associates with viral nucleoprotein complexes and is resistant to detergent treatment while APO3G packaged in the absence of viral genomic RNA is detergent sensitive and presumably not core associated (17). It is conceivable that the lack of antiviral activity of APO3G C288S/C291A when expressed from stably transfected HeLa cells is due to aberrant packaging of the protein into HIV-1 particles.…”
Section: Resultsmentioning
confidence: 99%
“…One fraction was left untreated; the other fraction was adjusted to 0.1% Triton X-100. Untreated and detergent-treated samples were layered on top of a 20% to 60% sucrose step gradient and subjected to ultracentrifugation as described previously (16,17). Four fractions (1.1 ml each) were collected from the top.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, A3G is not encapsidated by either HIV-1 virus-like particles that lack NC domains (Schafer et al 2004;Zennou et al 2004) or other retroviruses whose Gag proteins do not form complexes with A3G (Doehle et al 2006). The identity of the RNA(s) that promote A3G packaging in HIV-1 infected cells remains somewhat unresolved, though HIV-1 genomic RNA and 7SL RNA (a small pol III transcript that is found in the signal recognition particle, SRP) have each been assigned stimulatory roles in the process (Luo et al 2004;Khan et al 2005Khan et al , 2007Wang et al 2007). The fact that A3G is an avid RNA-binding protein ( Navarro et al 2005;Iwatani et al 2006) raises an important question concerning packaging: specifically, since A3G is associated with an array of cellular ribonucleoprotein (RNP) complexes in an RNA-dependent manner (Chiu et al 2005(Chiu et al , 2006Chelico et al 2006;Kozak et al 2006;Wichroski et al 2006;Gallois-Montbrun et al 2007), how can its RNA-binding site(s) be liberated to allow engagement with the RNA that facilitates packaging?…”
Section: The Packaging Of Apobec3g Into Hiv-1 Virionsmentioning
confidence: 99%
“…The current consensus view is that A3G packaging is determined by specific interactions between the N-terminal CDA domain of A3G and the nucleocapsid (NC) region of Gag that are also dependent upon the binding of A3G to RNA (Luo et al 2004;Schafer et al 2004;Svarovskaia et al 2004;Zennou et al 2004;Khan et al 2005;Navarro et al 2005;Burnett & Spearman 2007;Bogerd & Cullen 2008). Accordingly, A3G is not encapsidated by either HIV-1 virus-like particles that lack NC domains (Schafer et al 2004;Zennou et al 2004) or other retroviruses whose Gag proteins do not form complexes with A3G (Doehle et al 2006).…”
Section: The Packaging Of Apobec3g Into Hiv-1 Virionsmentioning
confidence: 99%
“…This interaction is further strengthened by A3G's propensity to bind single-stranded nucleic acids, particularly viral RNA at the plasma membrane site of virion budding (Schafer et al 2004;Svarovskaia et al 2004;Zennou et al 2004;Khan et al 2005;Burnett & Spearman 2007;Khan et al 2007;Soros et al 2007). The incorporation of only seven molecules of A3G into Dvif HIV virions produced by human peripheral blood mononuclear cells is sufficient to greatly impair HIV-1 replication (Xu et al 2007).…”
Section: Vif Circumvents Antiviral Activity Of Apobec3gmentioning
confidence: 99%